SISTEM KENDALI PENJEJAK SINAR MATAHARI DUA LINTASAN KEBEBASAN BERBASIS MIKROKONTROLER AT89C51 - Joko Purwono; Muchlas Muchlas; Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2008)
Instalation of solar cell panels permanently will not get maximum power point tracker (MPPT). To get the MPPT, the controlling of solar cell panels are needed in order to follow the direction of sun. In this paper, the design of control system of solar panel that capable to control of solar panel with 2 freedom track based on AT89C51 microcontroller is described. The movement is movement from east to west according to the earth rotation and movement from north to south in according to the earth revolution to get the MPPT. As a result, the prototype of design system has capable to control motor drive of solar cell panel, both automatically and manually with 2-line track to get MPPT.